(untitled) (Revista Apotheke, 2022)
I present, in this visual essay, a sequence of the first six drag-photoshoots that constitute the Studies for Eco series. These self-portraits marks processes of dilution and construction of my identities as Eco as I begin my journey in drag art, bringing different moments of scrutiny and tests on/about me that records the birth and transitions of this persona that leaves the paper and canvas where it used to live to now inhabit the world. I experiment different bodies and faces that are created from my memories, materials, music, experiences, stereotypes, books, memes and concepts indefinitely. In addition to these photoshoots, I visit the first nuances and efforts of Eco to show herself through drawings in our home phone book when we were nine years old - a fetus that is born in the drag-photoshoots sixteen years later. The visual essay ends with a letter received by Eco, offering possible interpretations and bridges between two subjectivities, two sensitivities, two stories that intersect in the same eagerness to continue existing and resisting.